Cascade Biocatalysis : Integrating Stereoselective and Environmentally Friendly Reactions - Riva, Sergio; Fessner, W.-D. (Wolf-Dieter); Wiley eBooks (Weinheim, Germany : Wiley-VCH, 2014)
This ready reference presents environmentally friendly and stereoselective methods of modern biocatalysis. The experienced and renowned team of editor have gathered top international authors for this book. They cover such emerging topics as chemoenzymatic methods and multi-step enzymatic reactions, while showing how these novel methods and concepts can be used for practical applications. Multidisciplinary topics, including directed evolution, dynamic kinetic resolution, and continuous-flow methodology are also discussed. From the contents:- Directed evolution of ligninolytic ox.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Biocatalysis; Catalysis; Enzymes -- Biotechnology; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Biocatalysis; Catalysis; Enzymes -- Biotechnology; Biokatalyse; Biotechnologie; Tandem-Reaktion; Electronic books